The effect of teacher multicultural attitudes on self-efficacy and wellbeing at work - Aalto, Sanni; Kankaanpaa, Reeta; Peltonen, Kirsi; Derluyn, Ilse; Szelei, Nikolett; Verelst, An; De Haene, Lucia; de Smet, Sofie; Spaas, Caroline; Jervelund, Signe Smith; Skovdal, Morten; Andersen, Arnfinn J.; et al. (SPRINGER, 2025)
Teachers are pivotal in creating safe and efficacious learning environments for ethnic minority students. Research suggests that teachers' multicultural attitudes, self-efficacy, and wellbeing at work may all play important roles in this endeavor. Using survey data on 433 teachers in Belgium, Denmark, Finland, Norway, Sweden, and the United Kingdom, the present study used structural equation models to analyze the paths between teachers' multicultural attitudes and work-related wellbeing (work dedication and exhaustion), and whether self-efficacy mediates these paths. We further investigated how these associations differ between teachers of reception classes for migrant and refugee students versus teachers of multi-ethnic mainstream classes. The results show that positive multicultural attitudes were directly associated with high level of work dedication, but not with work exhaustion. Self-efficacy mediated the association between multicultural attitudes and work-related wellbeing, indicated by both higher work dedication and lower work exhaustion. Concerning the role of teacher's class type, self-efficacy mediated the association between positive multicultural attitudes and work dedication for both types of teachers, whereas the mediation to low work exhaustion was only evident in mainstream class teachers. To conclude, teachers' multicultural attitudes and work-related wellbeing are mediated by self-efficacy and this important link should be acknowledged when designing professional development programs in order to create supportive and competent learning environments for all students.